Desenho universal e tecnologia assistiva: implementação de atividades pedagógicas para aluna com paralisia cerebral em classe comum - Almeida, Rita de Cássia Gomes de Oliveira (Universidade Federal de São Carlos, 2018)
At present, Brazil has advanced in legal documents regarding the inclusion of special education targeted students in terms of the access to regular school classrooms. The latest documents mention the provision of assistive technology resources (TA) to cerebral palsy students. One notices that a comprehensive part of these students need to use TA resources to enable their education process. Many teachers question the use of special resources with cerebral palsy students in regular classrooms. Thus, the general goal of the present study consisted of analyzing if the assistive technology resources, based on the universal design, could be used to meet cerebral palsy students’ education needs. To achieve this, the used research method followed the principles of qualitative approach, basing on collaborative research model, which data were collected through two tools, interview semi structured script and systematic observation. The participants of this study were a preschool education teacher of regular classroom, an education agent responsible for monitoring the cerebral palsy student in the regular classroom, a cerebral palsy student formally enrolled and attending these respective classes, and all other students of regular classroom. The procedures for data collection occurred in four stages, that are: first interview with the regular classroom teacher and education agent, implementation/intervention with TA resources through the universal design in the regular classroom, evaluation of assistive technology resources implemented in the regular classroom, and interview for the closure of the research with the regular classroom teacher and education agent. The results showed that the TA resources, in conformity with the universal design, were used in the regular classroom and, according to the teacher and education agent´s opinion, contributed to more dynamic in the classroom and learning for all students. However, it must be emphasized that for some activities, especially those which involved reading and writing, it was necessary to implement a specific TA resource for the cerebral palsy student. In general, the study showed the contribution to problem resolutions regarding the cerebral palsy student education process from the implementation and evaluation of assistive technology resources through the universal design, providing independency and autonomy in the learning of scholar contents.
Keywords: Educação especial; Desenho universal; Tecnologia assistiva; Paralisia cerebral; Special education; Universal design; Assistive technology; Cerebral palsy; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::CURRICULO; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO